Principles for improving modular simulators for practical training of air traffic controllers - Харченко, В.П.; Лазоренко, В.А. (Proceedings of National Aviation University (archive), 2007)
Main tendentious of module simulators improvements for air traffic controllers training are determined. Existent air traffic controllers simulator training has been analyzed and some deficiencies are detected. Method which helps to improve air traffic controllers training has been proposed. Principles of new method implementation into existent training system have been viewed.